Systematics and biogeography of Pleurobranchus Cuvier, 1804, sea slugs (Heterobranchia: Nudipleura: Pleurobranchidae) - Goodheart, Jessica A. (2015)
Species of Pleurobranchus (Mollusca: Gastropoda: Heterobranchia: Nudipleura: Pleurobranchidae) are commonly found worldwide, but there is a substantial amount of confusion regarding the ranges and identification of individual species. Difficulties in phylogenetic reconstruction and identification of pleurobranchids using morphological traits has resulted in complex classification schemes, with several species having disjunct ranges across physical and biogeographical barriers (including the tropical Indo‐Pacific, the eastern Pacific, and the Atlantic). A sizeable number of species of Pleurobranchus has been described; however, many of these species are morphologically and biogeographically similar to others, and probably constitute synonyms. This paper provides a phylogenetic framework of classification for Pleurobranchus based on the mitochondrial genes cytochrome c oxidase I (COI) and 16S rDNA and the nuclear gene histone 3 (H3) using Bayesian and maximum likelihood approaches. Molecular phylogenies obtained recovered most of the well‐established species of Pleurobranchus and some morphological characters were found to have taxonomic value for delimiting species in this group. Automatic barcode gap discovery (ABGD) analyses substantiated the distinctiveness of units/species recovered in the phylogenetic analyses, with some exceptions. Morphological descriptions for the 14 species recovered in the molecular phylogeny and discussions on the biogeography and colour variation are included.